Effects of corn oil on the gastric mucosa of horses with induced ulcer (2016)
ABSTRACT: equine gastric ulcer syndrome (EGUS) has a multifactorial nature and it affects both the squamous and glandular mucosa of the stomach. Multiple therapeutic strategies involving large periods of medication are used to treat this condition. Objective: to evaluate the effects of administering corn oil (CO) to horses with induced gastric ulcers, and to describe the mechanism of action of the mucosal repair. Methods: fifteen horses divided into three groups were used. A combination of confinement and phenylbutazone was used during the ulcer-induction phase. After the gastroscopic evaluation and laboratory tests, animals were treated with sucralfate (SA; group I), and CO at doses of 70 and 90 mL/100 Kg (groups II and III, respectively). Gastroscopy, gastric content collection, and biopsy of the glandular mucosa were performed to analyze prostaglandin E2 (PGE2), pH, and antioxidant and oxidant parameters. Results: mild to moderate gastric lesions were induced in the glandular and non-glandular mucosa. Among the mechanisms of the treatments, reestablishment of the antioxidant parameters and inhibition of myeloperoxidase (MPO) oxidant enzyme were prominent, but PGE2 concentration had a weak influence. Conclusion: similarly to SA, CO only had therapeutic effects in the glandular mucosa.